DESIGN AND DEVELOPMENT OF STUBBLE SELLING AND ASSISTANCE APPLICATION - Patil, Harshali; Agrawal, Aakanksha; Jain, Jinal; Gupta, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Every year, Punjab and Haryana burn between 15 and 20 million tonnes of crop residue, the majority of which is rice straw. Agricultural burning produces a large amount of smoke quickly. Delhi’s air pollution levels during Punjab’s busiest crop-burning season are 20 times higher than what the World Health Organization considers to be safe (WHO). Many states forbid burning of stubble, and some farmers have even been detained as a result. However, they do so because they have a short window of time between the paddy crop’s harvest and threshing, and the wheat crop’s field preparation and planting. Therefore, to provide a one stop solution to stubble burning, a platform where businesses that buy stubble can be connected can be farmers that sell stubble. Additionally, if the farmers are unable to sell the stubble, they can connect them with NGOs or agricultural institutes that can provide better solutions depending on type of crop, soil, etc. In this way, it will help farmers in generating additional income and can also improve quality of air.